Measurement of plasma lysophosphatidic acid concentration in healthy subjects: strong correlation with lysophospholipase D activity - Hosogaya, Shigemi; Yatomi, Yutaka; Nakamura, Kazuhiro; Ohkawa, Ryunosuke; Okubo, Shigeo; Yokota, Hiromitsu; Ohta, Masato; Yamazaki, Hirokazu; Koike, Toru; Ozaki, Yukio (Annals of clinical biochemistry, 2008)
Lysophosphatidic acid (LPA) plays important roles in a variety of biological responses, especially in the area of vascular biology, and the determination of its plasma concentration is believed to be important. Several mechanisms are known to be involved in the metabolism of LPA. To identify factors that may determine the plasma concentrations of this important bioactive lipid, we examined its concentrations using an enzymatic cycling assay and related parameters in 146 healthy subjects. The LPA concentration was significantly higher in women (mean +/- SD, 0.103 +/- 0.032 micromol/L; n = 47) than in men (0.077 +/- 0.026 micromol/L; n = 99). A multiple regression analysis showed a strong positive correlation between the plasma LPA concentration and serum lysophospholipase D (lysoPLD) activity, while the LPA concentration was correlated with the plasma lysophosphatidylcholine (LPC) concentration only in men. Other lipid-related parameters were only slightly correlated or were not correlated with the LPA concentration. Our findings suggested that conversion from LPC by lysoPLD might be the major route for LPA production in plasma.